Question Number 105207 by Anindita last updated on 26/Jul/20

99−98((98)/(99)) = ?  Can you solve this?

Commented byqwerty111 last updated on 26/Jul/20

98+((99)/(99))−98−((98)/(99)) = (1/(99))

Commented byJDamian last updated on 26/Jul/20

do you assume   a(b/c)  means   a+(b/c)?

Commented byJDamian last updated on 27/Jul/20

I never used/understood  a(b/c) = a+(b/c) in  algebra/maths texts. I only found in, for  instance, cooking recipes books (♮2 1/2  teaspoonε)

Answered by Aziztisffola last updated on 26/Jul/20

99((99)/(99))−98((98)/(99))=99((98+1)/(99))−98((98)/(99))  =(98+1)((98+1)/(99))−98((98)/(99))=98((98)/(99))+((2×98)/(99))+(1/(99))−98((98)/(99))  =((2×98+1)/(99))=((196)/(99))

Commented byAziztisffola last updated on 27/Jul/20

I know that a+(b/c)≠a×(b/c)  ax=a×x not a+x.

Commented byPRITHWISH SEN 2 last updated on 27/Jul/20

98×((98)/(99))+((2×98)/(99))+(1/(99))−98((98)/(99)) ≠ ((2×98+1)/(99))  as 98×((98)/(99)) ≠98((98)/(99))

Commented byPRITHWISH SEN 2 last updated on 27/Jul/20

2(1/3)=(7/3)  2(1/3) = 2+(1/3)=(7/3)  2(1/3)=2×(1/3)= (2/3)  ∴ 2(1/3)= 2+(1/3) ≠ 2×(1/3)  ∴ you are wrong

Commented byqwerty111 last updated on 26/Jul/20

 ★   98 ((98+1)/(99 ))   ★

Commented byAziztisffola last updated on 26/Jul/20

Just a simple calculus.

Commented byqwerty111 last updated on 26/Jul/20

Ok

Commented byAziztisffola last updated on 26/Jul/20

I assume a(b/c)=a×(b/c) not a+(b/c)